2012
DOI: 10.1063/1.4773492
|View full text |Cite
|
Sign up to set email alerts
|

Radiofrequency plasma antenna generated by femtosecond laser filaments in air

Abstract: International audienceWe demonstrate tunable radiofrequency emission from a meter-long linear plasma column produced in air at atmospheric pressure. A short-lived plasma column is initially produced by femtosecond filamentation and subsequently converted into a long-lived discharge column by application of an external high voltage field. Radiofrequency excitation is fed to the plasma by induction and detected remotely as electromagnetic radiation by a classical antenna

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
35
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 60 publications
(35 citation statements)
references
References 23 publications
0
35
0
Order By: Relevance
“…An avalanche induced breakdown would lead to a high density hot plasma that would behave like a metallic antenna, as demonstrated in ref. [6]. In conclusion, we have shown evidence of the coupling of microwave radiation to a multi-filament plasma column and its propagation out of the excited region of the plasma in the form of a TM wave.…”
mentioning
confidence: 87%
See 1 more Smart Citation
“…An avalanche induced breakdown would lead to a high density hot plasma that would behave like a metallic antenna, as demonstrated in ref. [6]. In conclusion, we have shown evidence of the coupling of microwave radiation to a multi-filament plasma column and its propagation out of the excited region of the plasma in the form of a TM wave.…”
mentioning
confidence: 87%
“…It can also trigger and guide meter long electric discharges [4], allowing contactless transfer of large currents [5]. In turn, long-lived guided discharges can act as virtual antennas [6] or could improve the aerodynamics of fast moving object through atmosphere [7].…”
mentioning
confidence: 99%
“…20 On the other hand, the RF wave of sufficiently high power can lead to electron heating and affect the collision frequency, and thus, the plasma channel conductivity and lifetime favorably. 10 According to the review work of Moisan and Zakrzewskit, 22 an estimate of minimum input wave power to sustain a surface-wave discharge under subatmospheric pressure P min ¼ pa 2 hn D =2aðn D Þ can be used as a reference, where a is plasma radius, h-power lost by an average electron in collisions of all kinds, n D -the density at the end of the column, and aðn D Þ-wave attenuation coefficient, respectively. More realistically, following the experimental result of Rayner et al, 3 Dwyer 7 and Brelet et al, 10 the RF power level to start influencing the plasma condition greatly is evaluated to be a kilowatt level for the atmospheric-pressure plasma, long antenna case.…”
Section: Physics Of Laser-induced Plasma Channel Antennamentioning
confidence: 99%
“…Mechain et al 8 studied the electromagnetic emission from a plasma column generated by a chirped pulse amplified laser system emitting pulses at a repetition rate of 10 Hz by using a reception antenna active in the region 10 kHz-30 MHz, and Marquis 9 has proposed a device for effective coupling between a laser-induced plasma channel antenna and a power signal generator. Brelet et al 10 have demonstrated tunable radiofrequency emission from a meterlong linear plasma column produced in air at atmospheric pressure. Radiofrequency excitation is fed to the plasma by induction and detected remotely as electromagnetic radiation by a classical antenna.…”
Section: Introductionmentioning
confidence: 99%
“…Femtosecond laser filamentation has raised much interest in the last decade in various domains of applied physics such as guiding electric discharges [1,2], atmospheric monitoring through LIDAR technique [3], Terahertz generation [4], white-light continuum generation [5] or virtual radiofrequency antenna [6]. Resulting from a dynamic competition between the Kerr effect and plasma defocusing, filamentation appears spontaneously during the propagation of an intense femtosecond laser pulse, provided the initial peak power exceeds a threshold value P cr (a few GW in gases).…”
Section: Introductionmentioning
confidence: 99%